Toll-like receptor gene polymorphism and its relationship with somatic cell concentration and natural bacterial infections of the mammary gland in sheep - Swiderek, W P; Bhide, M R; Gruszczyńska, J; Soltis, K; Witkowska, D; Mikula, I (Folia microbiologica, 2006)
Possible correlation between Toll-like receptor (TLR)-gene mutations and the susceptibility of the mammary gland to bacterial infections and also the associate breed-dependent aspects of somatic cell concentration (SCC), bacterial infection and TLR-gene mutations in sheep are described. In Polish Lowland Sheep (PLS), milk samples exceeding the level of 500/microL (i.e. 5 x 10(5) per mL) of SCC were recorded almost twice more frequently than in Polish Heath Sheep (PHS) (40 and 22.3%, respectively). The frequency of bacterial infections was also found in a similar ratio (20 and 12.7%, respectively). During detection of the TLR-gene mutation we recorded 2 alleles of TLR1, 6 alleles of TLR2 and 10 alleles of TLR4 genes in PHS sheep, while PLS sheep possessed 2, 4 and 6 alleles, respectively. Statistical analyses revealed a relationship between the specified TLR alleles, SCC and the frequency of incidence of bacterial inflammations of mammary gland. The data may serve as a benchmark for further study of TLR-gene mutation-dependent predisposition of mammary gland defensive cells to recognize the pathogen properly and initiate the immunological response, and may help in identifying one of the markers of natural resistance against sheep mastitis.
Keywords: mléčné žlázy zvířat; alely; Sheep; Mammary Glands, Animal; Toll-Like Receptors; polymorfismus genetický; bakteriální infekce; frekvence genu; Alleles; zvířata; Polymorphism, Genetic; toll-like receptory; Sheep Diseases; Milk; Genetic Predisposition to Disease; genetická predispozice k nemoci; Gene Frequency; Bacterial Infections; Animals; mléko; nemoci ovcí; ovce